Effect of Chair aerobics as low intensity exercise training on heart rate, blood pressure and six minute walk distance in post coronary artery bypass graft surgery patients through phase I cardiac rehabilitation - Thapa, Shaili; Pattanshetty, Renu B. (Nepalese Heart Journal, 2016)
Background and Aims: Cardiac Rehabilitation after Coronary arteries bypass graft (CABG) surgery is known to have several favorable effects. Aerobics exercise in the form of chair aerobics shown to have beneficial effects with little evidence. The purpose of the present study was to demonstrate the effect of chair aerobics as low intensity exercise training in heart rate, blood pressure and six minute walk distance in post CABG patients during phase I cardiac rehabilitation.   Methods: It was a single centre, prospective study carried out in Indian tertiary care set-up. Fifty patients post CABG patients were included. Chair aerobics as a low intensity exercise training was given.  Pre and post-exercise outcome measurements in the form of heart rate, blood pressure and six-minute walk distance test were recorded. Results: The study showed statistically significant difference in systolic blood pressure (p= 0.018), heart rate (p≤0.001) and increase in six minute walk distance (p≤0.001). Conclusion: Chair aerobics as low intensity exercise training demonstrated improvement in heart  rate, systolic blood pressure and six minute walk distance test in subjects with CABG through phase I  cardiac rehabilitation.  Nepalese Heart Journal 2016; 13(1) 19-23